Politeness in Roasting: When Humour Meets Power - Yusuf Al Arief (CV. Rustam, 2023)
This research examines the use of politeness strategies in stand-up comedy roasts. Specifically, it examines how comedians manage power dynamics and societal standards of politeness while addressing those in authoritative positions in a given society. The author investigated stand-up comedy roasting using Brown and Levinson's politeness theory and prior research on humor and impoliteness. The results indicate that comedians used politeness methods, including compliments or flattery, indirectness or hedges, and off-the-record discourse, to achieve their humorous objectives. Using the politeness strategies theory, this research provides insights into how comedians utilize language and humor to manage challenging social situations.